Best Time for Laparoscopic Cholecystectomy Following Endoscopic Sphincterotomy Post Endoscopic Retrograde Cholangiopancreatography: A Prospective Observational Study - Muhammed Dewana , Azhy (Diyala Journal of Medicine, 2022)
Background: Choledocholithiasis occurs in 10–15% of patients with symptomatic gallstones. Stones in the common bile duct ought to be removed to avoid complications like acute pancreatitis and cholangitis. Objective: To estimate the timing of Laparoscopic cholecystectomy after endoscopic sphincterotomy (post endoscopic retrograde cholangiopancreatography) and its outcomes. Patients and Methods: A clinical prospective comparative study was done in the Surgical Department of Rizgary Teaching Hospital in Erbil during the period from 1st of January 2019 to 1st of December 2021 on a sample of 50 patients with Common Bile duct stones categorized into two groups; group I (25) patients who underwent laparoscopic cholecystectomy within 72 hours of ERCP (early), while (25) patients with laparoscopic cholecystectomy beyond 3 days (1-6 weeks) of ERCP were included in group II (delayed). Results: Mean surgical duration for group I patients was significantly shorter than the mean surgical duration for group II patients (p=0.02). The mean hospital stay duration for group I patients was markedly shorter than the mean hospital stay duration for group II patients (p<0.001). There was an obvious association between the two groups regarding wider cystic duct, and intraoperative adhesions.Both findings were found more in group II. Conclusion: Earlier laparoscopic cholecystectomy after endoscopic retrograde cholangiopancreatography has better intraoperative and postoperative outcomes than delayed laparoscopic cholecystectomy.